2014
DOI: 10.1007/s10157-014-1046-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio as a predictor of cardiovascular events in incident dialysis patients: a Japanese prospective cohort study

Abstract: A higher neutrophil/lymphocyte ratio is associated with increased risk of cardiovascular disease events and is a stronger predictor of future events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
1
32
1
Order By: Relevance
“…In a previous study, the blood sample was collected just before the first dialysis session, and the authors evaluated the relationship between blood sample data and all-cause and cardiovascular mortality [6]. Thus, we collected the blood sample using a similar method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, the blood sample was collected just before the first dialysis session, and the authors evaluated the relationship between blood sample data and all-cause and cardiovascular mortality [6]. Thus, we collected the blood sample using a similar method.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we focused on this new marker, which has never been evaluated in the nephrology and dialysis fields. The risks of the incidence of CVD events associated with several readily measured indicators have been evaluated, including the highly sensitive C-reactive protein level [4], increased troponin level [5], and neutrophil-lymphocyte ratio [6]. Recently, serum Mg has been reported as a predictor of all-cause and cardiovascular mortality in patients on maintenance and initial HD [7].…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, based on the NISE study, we reported that a higher NLR was associated with higher risk of CVD in 86 incident dialysis patients with a median follow-up of 38.7 months [3] . The main finding of that study was that a higher NLR was associated with increased risk for CVD-related events, both in terms of shorter duration from the start of the dialysis therapy to the first CVD event and a large number of cumulative CVD events during the follow-up time.…”
Section: Potential Role Of Nlr As An Inflammatory Biomarkermentioning
confidence: 99%
“…Since releasing our report [3] , the number of studies on NLR has been increasing in the fields of cancer, atherosclerotic disease including CVD in CKD patients. In 2004, Rifaioglu et al reported that NLR was higher in patients with Behçet disease compared with healthy subjects, and that increased NLR correlated with disease activity [45] .…”
Section: Potential Role Of Nlr As An Inflammatory Biomarkermentioning
confidence: 99%
See 1 more Smart Citation